Association between mean platelet volume and major adverse cardiac events in percutaneous coronary interventions: a systematic review and meta-analysis. Issue 8 (December 2020) - Chen, Zhongxiu; Li, Nan; Wang, Jing; Li, Chen; He, Sen; Zhou, Xiaorong; He, Yong
Abstract : Platelets with high hemostatic activity play a key role during percutaneous coronary interventions (PCI), and in recent years, mean platelet volume (MPV) has been looked upon as a crucial indicator of platelet reactivity. Thus, MPV may emerge as a potential gauge for the measurement of major adverse cardiac event (MACE) risks in PCI patients. This study aimed to conduct a meta-analysis illustrating the association between MPV and long-term MACE in PCI. The Cochrane Library, Pubmed, EMBASE, Ovid MEDLINE, and BIOSIS databases were used to search for relevant studies from their inception to 30 June 2019. All studies reporting incidences of MACE and MPV in PCI patients were retained. Data extraction was performed by three independent reviewers. A total of 33 studies were included in this meta-analysis. The results indicated that patients with MACE had a significantly larger MPV than those without, with an unstandardized mean difference (USMD) of 0.29 fL (95% CI, 0.04–0.54). The USMD of MPV in deceased patients was 0.39 fL (95% CI, 0.09–0.68). The results also indicated that patients with larger MPV were at greater risks of having MACE and higher incidence of mortality than those with smaller MPV, with a pooled risk ratio of 1.81 (95% CI, 1.29–2.55) and 2.34 (95% CI, 1.52–3.60), respectively. These findings indicate a significant association between larger MPV and MACE in PCI patients. Consequently, MPV, an easily accessible indicator, might be helpful in PCI patients' risk assessment and stratification. Abstract : Supplemental Digital Content is available in the text.